Business model innovation and transition to a sustainable food system: A case study in the Lisbon metropolitan area - Salavisa, I. (2022)
The food systems’ transition towards a sustainable involves structural changes, namely the emphasis on local production, short supply chains, and the preference for organic products. The shift in the agri-food system is taking place through the creation of entirely new businesses and individual farms moving towards organic production. In both cases, the enterprises use a combination of well-established agricultural knowledge and techniques, new scientific knowledge on productive methods and new technological platforms for commercialization. These mixed sources permit the creation of innovative business models (BMs). They exemplify how traditional industries can absorb/generate innovation at technological and organizational levels, and become part of the new knowledge-based era. The study has three objectives: to analyse the emerging agri-food businesses in the Lisbon Metropolitan Area (LMA); to characterize innovative sustainable BMs within the transition dynamics; to reflect on the challenges that the characteristics of the food system pose for the emergence of these BMs. The study is part of an interdisciplinary project on Spatial Planning for Change (SPLACH). The analysis addresses the food system transition in a specific territory, namely the LMA. The paper presents results of the research conducted, focusing on the case of an organic food initiative, Quinta do Oeste.